The Influence of Content, Credibility, and Muslim Celebrity Endorsers on Buying Interest with Brand Image as a Mediation Variable - Athaya Azaria Malik; Yudha Trishananto (Universitas Tidar, 2022)
The phenomenon of many entrepreneurs who want to attract consumers through social media by using a celebrity that has credibility and demands to advance their brand. One of the celebrities who are loved today is Aghnia Punjabi with her trademark wearing a hijab. Indonesia is a country where the majority of the population is Muslim. From this phenomenon, researchers want to find out whether there is a relationship between Instagram content, credibility, and Muslim celebrity endorsers on consumer buying interest with brand image as a mediating variable. This study aims to: determine the effect of content; credibility; and Muslim celebrity endorser Agnia Punjabi on buying interest and brand image. Then to determine the effect of brand image in mediating content, credibility, and celebrity endorser Muslim Aghnia Punjabi on buying interest. This research is a quantitative type using a sample of FEBI IAIN Salatigga students. The type of data used is only primary data and will be analyzed by t test, F test and Path Analysis. The results showed that Instagram content, credibility and celebrity endorser Muslim Aghnia Punjabi had a significant and significant effect on buying interest and brand image. However, Muslim celebrity endorsers have no significant and significant effect on brand image. Then brand image is able to mediate the relationship of content and credibility to buying interest. Then the results obtained that brand image cannot mediate the relationship of Muslim celebrity endorsers to consumer buying interest.